Hubungan Dukungan Orang Tua dengan Harga Diri Remaja di SMK Raflesia Depok - Izni Rachma Nilamsari; Nita Sukamti; Nur Fajariyah (Malahayati Nursing Journal, 2024)
ABSTRACT Adolescence is the age range from 10 to 19 years where a person's development includes significant physical, cognitive and psychosocial growth. At this stage, the role of parents becomes very crucial in providing the support needed to form positive self-esteem and create a high level of self-esteem. This study aims to determine the relationship between parental support and self-esteem in adolescents at Raflesia Vocational School, Depok. This study used a cross sectional research design with random sampling technique involving 162 respondents. The research instrument consists of a bullying questionnaire, support from parents, peers and a self-esteem questionnaire which has been tested for validity and reliability with Cronbach's alpha Cronbach's alpha standard. Data were analyzed using chi-square to determine whether there was a relationship between variables. The research results show that there is a significant relationship between the independent variable (parental support) and the dependent variable (adolescent self-esteem). There is a significant relationship between parental support and self-esteem in adolescents with a ρ value 0.05. Keywords: Parental Support, Self-Esteem of Adolescent Peers ABSTRAK Masa remaja adalah rentang usia 10 hingga 19 tahun di mana perkembangan seseorang mencakup pertumbuhan fisik, kognitif, dan psikososial yang signifikan. Pada tahap ini, peran orang tua menjadi sangat krusial dalam memberikan dukungan yang diperlukan untuk membentuk harga diri yang positif dan menciptakan tingkat harga diri yang tinggi. Penelitian ini bertujuan untuk mengetahui hubungan dukungan orang tua dengan harga diri pada remaja di SMK Raflesia Depok. Pada penelitian ini menggunakan desain penelitian cross sectional dengan random sampling technique yang melibatkan 162 responden. Instrument penelitian terdiri dari dukungan orang tua dan kuesioner harga diri yang telah diuji validitas dan reliabilitas dengan nilai cronbach’s alpa cronbach alpha standart. Data dianalisis menggunakan chi-square untuk mengetahui adanya hubungan antar variabel. Hasil penelitian menunjukan bahwa terdapat hubungan yang signifikan antara variable independen (dukungan orang tua) dengan variable dependen (harga diri remaja). Terdapat hubungan yang signifikan antara dukungan orang tua dengan harga diri pada remaja dengan nilai ρ value 0,05. Kata Kunci: Dukungan Orang Tua, Harga Diri Remaja